First-year secondary mathematics teachers' metacognitive knowledge of communication activities. (3rd July 2019) - Raymond, Kate Meredith
ABSTRACT: Research has documented that mathematics teachers rarely use communicative activities; activities that allow for the sharing of ideas and clarification of understandings (NCTM, 2000). Teacher metacognitive awareness provides a possible framework for understanding the difficulties secondary mathematics teachers face when attempting to incorporate communicative activities. Without metacognitive knowledge and awareness about communicative activities, teachers lack the understanding of the purpose of such activities, procedures used to implement such activities successfully, and/or the conditions under which such activities are useful. This case study analyzed the metacognitive knowledge and awareness of two first-year high school mathematics educators by asking what metacognitive knowledge and awareness of communicative activities did the participants have or were developing and what experiences helped the participants to develop this knowledge. Findings indicate that the participants believed used communicative activities in their classrooms. However, the communicative activities used by the participants rarely engaged students in communicating about their understandings of mathematics; instead, the participants engaged their students in communicative activities in order to construct classroom norms or to shift the responsibility for learning to the students. Thus, while the participants clearly demonstrated declarative knowledge of communicative activities, their procedural and condition knowledge, that is how, when, and why to use such activities, was not well formed. These finding suggest that more emphasis is needed on developing pre-service teachers procedural and conditional metacognitive knowledge of communicative activities. In addition, more qualitive research on mathematics teachers' understanding of communicative activities is needed.